1999
DOI: 10.1111/j.1600-0765.1999.tb02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human platelet‐derived growth factor‐BB and bone morphogenetic protein‐2 application to demineralized dentin on early periodontal ligament cell response

Abstract: The purpose of this study is to investigate the early responses of human periodontal ligament cells attached to recombinant human platelet-derived growth factor-BB and bone morphogenetic protein-2 applied EDTA-demineralized dentin. One hundred and seventy-four root-planed flat dentin blocks were prepared from the mid-third of periodontally diseased human tooth roots. After demineralization with 24% EDTA (pH 7.02) 120 dentin blocks were treated with 0.5 and 1 microgram/ml rhPDGF-BB, 1 and 3 micrograms/ml rhBMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
5
29
0
1
Order By: Relevance
“…Similar findings were observed in studies carried out by Belal et al (2006), Zaman et al (1999). On day 7, Group 4 also showed slight increase in number of cells (50 AE 8.9) attached.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings were observed in studies carried out by Belal et al (2006), Zaman et al (1999). On day 7, Group 4 also showed slight increase in number of cells (50 AE 8.9) attached.…”
Section: Discussionsupporting
confidence: 89%
“…Fibroblasts have shown maximum proliferative as well as chemotactic response to PDGF-BB homodimer (Oates et al, 1993). Exogenous addition of PDGF has shown to significantly improve cell migration, cell proliferation and the mitotic activity of PLFs, (Oates et al, 1993) but little is known about the influence of PDGF-BB on the morphology of fibroblasts in spite of the innumerable research done on rhPDGF-BB (Belal, 2006;Gamal et al, 1998;Jayakumar et al, 2011;Mumford et al, 2001;Nevins et al, 2003Nevins et al, , 2005Oates, 1993;Sant'Ana et al, 2007;Sarment et al, 2006;Zaman et al, 1999). An assessment of the influence of PDGF-BB on the morphology of PLFs can provide added information to the existing literature about the influence of rhPDGF-BB on PLFs.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant improved regenerative capability could be related to increased recruitment of progenitor MSC, which subsequently differentiate to form PDL tissue. Recently, PDLSC transfected with expression vectors for platelet-derived growth factor and bone morphogenetic protein were investigated in periodontal tissue engineering models (40). These studies revealed the regeneration of normal periodontal tissues, containing organized cementum, alveolar bone and the PDL attachment apparatus.…”
Section: Dental Pulp Stem Cells and Dental Tissue Engineeringmentioning
confidence: 99%
“…The application of recombinant human platelet-derived growth factor and recombinant human bone morphogenetic protein-2 to EDTA demineralized dentin surfaces promotes early human periodontal ligament cell responses by increasing cell proliferation and differentiation, ultimately enhancing periodontal regeneration (Zaman et al, 1999). More recently, Zhu et al (2001) have demonstrated that Ad2/platelet-derived growth factor can effectively transduce cells derived from the periodontium and can promote biological activity equivalent to platelet-derived growth factor-AA.…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%